Analysing Grammar Errors in Malay Language Learning - Isabella, Jali (UNIMAS Publisher, 2021)
This study aims to describe the grammatical errors in an analysis of a Malay language course assignment. It focuses on several local students who enrolled on MPU3312 Malay Language course at a public university in Semester 1, 2020/2021 session. The study was conducted on 250 students, using scripts from their group assignment, namely Text Error Analysis Task (Tugasan Analisis Kesalahan Teks). A total of 25 samples of student assignments were analysed and described using Corder Error Analysis Theory. Findings show that students committed 79 types of grammatical errors. Errors in the orthographic (ortografi) aspect are the most common. Preposition (Kata sendi nama) errors and redundancy (kelewahan) were also distinctively found in the writing samples. There were also other types of grammatical errors identified, such as copular verb (kata pemeri), "ianya", abbreviation (singkatan), affix (imbuhan), and word choice (pemilihan kata). The study has brought an understanding of the nature of typical grammatical errors in Malay language writing at the university.